The Effect of Quercetin on the Physiological Funtions of Rats Peripheral Plood Neutrophils in Vitro Condition - A Notaj; SM Abtahi Froushani; Sh Khezri (Armaghane Danesh Bimonthly Journal, 2016)
Background & aim: In traditional medicine, medicinal plants containing flavonoid compounds were used for several years in the treatment of various diseases. Quercetin is one of the flavonoid composition family that has a maximum antioxidant flavonoid content. The aim of this study was to investigate the physiological features of rats peripheral blood neutrophils treated with quercetin.